Neighborhood and Individual Sociodemographic Characteristics Associated with Disparities in Adult Obesity and Perceptions of the Home Food Environment - Michael T. Halpern; Michael T. Halpern; Laura C. Arena; Rachel A. Royce; Robin E. Soler; Breda Munoz; Caitlin M. Hennessy (Mary Ann Liebert, 2017)
Purpose: Multiple studies have demonstrated significant disparities in the relationship between individual sociodemographic characteristics and risk of overweight or obesity. However, little information is available for assessing the complex associations among being overweight or obese with neighborhood and individual sociodemographic factors and the measured and perceived community food environment. Methods: Using 2014 national evaluation data from 20 communities (analyzed 2015?2016) that participated in the U.S. Centers for Disease Control and Prevention Community Transformation Grants Program, we used multilevel multivariable models to assess associations among factors at the individual, census tract, and county levels with being overweight or obese and with the perceived home food environment. Results: Individual level factors (age, sex, race/ethnicity, household income, and education) were significantly associated with the likelihood of being overweight or obese in every model tested. Census tract level poverty and education were significantly associated with the likelihood of being overweight or obese in univariate but not multivariable analyses. Perceived community food environment was a significant predictor of the perceived home food environment; the objective measure of county-level grocery store access was not. Neither perceived nor objective community food environment measures were significantly associated with overweight/obesity in multivariable analyses. Conclusion: Individual-level sociodemographic characteristics are more strongly associated with obesity-related outcomes than are area-level measures. Future interventions designed to address health equity issues in obesity among underserved populations may benefit from focusing on nutrition education tailored to individuals, to encourage purchase and consumption of healthy food. Improving healthy food availability in underserved communities may also be critical for nutrition education to have a meaningful impact.